2022
DOI: 10.1177/09603271221074346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of butein on human osteosarcoma cell proliferation, apoptosis, and autophagy through oxidative stress

Abstract: Purpose Osteosarcoma (OS) is a primary malignant bone tumor, and the cure rate has stagnated in the past three decades. Butein, a plant polyphenol extracted from many herbs, has been proved to possess anti-tumor activity. However, the effect of butein on human OS and the underlying mechanisms remain to be elucidated. Materials and Methods The OS cell line 143B was used. The effects of butein were evaluated through the cell proliferation assay, flow cytometry, florescence and transmission electron microscopy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In both in vitro and in MG-63-induced xenograft mice, results were consistent in showing that combined treatment with ononin, or DOX blocked the EGFR-Erk1/2 cascade regulatory pathway. This present study was consistent with reports from earlier studies that treatment with Polygonum cuspidatum, curcumin, and butein inhibited the EGFR-Erk1/2 cascade signaling pathway, resulting in the inhibition of osteosarcoma [39][40][41]. The ononin did not adversely affect the liver and kidney in the histological and AST/ALT studies, which indicates that it is a safe molecule.…”
Section: Discussionsupporting
confidence: 93%
“…In both in vitro and in MG-63-induced xenograft mice, results were consistent in showing that combined treatment with ononin, or DOX blocked the EGFR-Erk1/2 cascade regulatory pathway. This present study was consistent with reports from earlier studies that treatment with Polygonum cuspidatum, curcumin, and butein inhibited the EGFR-Erk1/2 cascade signaling pathway, resulting in the inhibition of osteosarcoma [39][40][41]. The ononin did not adversely affect the liver and kidney in the histological and AST/ALT studies, which indicates that it is a safe molecule.…”
Section: Discussionsupporting
confidence: 93%
“…The study reported that the effect of the GANT61/miR-1286/RAB31 axis on inhibition OS was to induce oxidative stress [21]. And butein induced oxidative stress in OS cells to promote cell autophagy and apoptosis [22]. In addition, allicin could promote cell apoptosis and autophagy by increasing the accumulation of ROS [15].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Yang et al reported that butein induces apoptosis in ovarian cancer cells by activating both exogenous and endogenous pathways 35 . Additionally, Zhang et al illustrated how butein regulates oxidative stress, activates the JNK signaling pathway and blocks the Akt/mTOR signaling pathway, thereby inducing apoptosis and autophagy in osteosarcoma cells 36 . Recent research has further unveiled butein’s remarkable antitumor potential in CRC.…”
Section: Discussionmentioning
confidence: 97%